AGRI-ENVIRONMENTAL INDICATORS IN THE EU: MEASURING DISCREPANCIES ACROSS MEMBER STATES - Pantović, Danijela; Pantić, Nemanja; Lukovic, Milica; Dudić, Branislav (Economics of Agriculture, 2026)
The paper analyzes agri-environmental indicators of EUcountries from 2017 to 2023 to assess progress towardsustainable agriculture. Using descriptive statistics,principal component analysis (PCA), and a compositeindex, it identifies key sustainability dimensions and ranksEU countries by performance. Results indicate reducedagricultural greenhouse gas emissions, growth in renewableenergy production, and expansion of organic farmingareas. However, pesticide sales and related environmentalrisks remain high, highlighting ongoing dependence onchemical inputs. PCA reveals two main components: thefirst reflects energy and agricultural sustainability, whilethe second captures ecological risks linked to pesticideuse and emissions. The composite index shows cleardisparities among EU countries—some have advanced,while others lag behind the EU average. Findings suggestthat EU agricultural policy should intensify pesticidereduction efforts while continuing to promote renewableenergy and organic farming initiatives.